Perbedaan Kepuasan Pernikahan Ditinjau dari Peran dalam Pernikahan pada Individu yang Menikah Muda - Zym, Nibras Adila Abrar; Dahlia, Dahlia; Afriani, Afriani; Sari, Novita (JIWA: Jurnal Psikologi Indonesia, 2024)
The phenomenon of divorce in couples who marry young is considered related to marital satisfaction. Marital satisfaction is both a husband and wife's subjective evaluation of marriage. One factor that affects marital satisfaction is the role in the marriage. This study used quantitative research methods with a comparative approach. This research aims to see differences in marital satisfaction in terms of roles in marriage in individuals who married young. Sampling using nonprobality sampling techniques with a total of 120 research respondents. Normality test using Kolmogorov-Smirnov and obtained significance value (p)=0.000 (p<0.05). The homogeneity test uses the Test of Homogeneity of Variances (Levene Test) and obtained a significance value p=0.062 (p>0.05). The hypothesis test was carried out using the Mann-Whitney technique and obtained a significance value (p)=0.046 (p<0.05). The results of the study showed that there were differences in marital satisfaction in terms of the role of marriage in individuals who married young.